The role of fiscal transfers for regional economic convergence in Europe - Cristina Checherita-Westphal; Christiane Nickel; Philipp Rother (European Central Bank (ECB), 2009)
This paper provides evidence on the role of net fiscal transfers to households and EU structural funds for per-capita output convergence across a large sample of European regions during the period 1995-2005. We find that net fiscal transfers, while achieving regional redistribution, seem to impede output growth and promote an “immiserising convergence”: output growth rates in poor receiving regions decline by less than in rich paying regions. EU structural and cohesion funds spent during 1994-1999 had a positive, but slight, impact on future economic growth, mainly through the human development component.
Keywords: E62; R11; R23; 330; convergence; Fiscal Policy; regional economic growth; regional migration; Finanzpolitik; EU-Strukturfonds; EU-Strukturfonds; Binnenwanderung; Regionales Wachstum; Wirtschaftliche Konvergenz; EU-Staaten